Tecnologias digitais na formação inicial em Letras: um olhar para a prática de ensino e para o estágio supervisionado - Oliveira, Luana Rodrigues de Souza (2025)
Considering the challenge of integrating Digital Technologies (DT) into the initial training of teachers and the gap between the discourse on the importance of technology and its effective implementation in undergraduate language teacher education programs, this research posed the following question: how can the integration of DT, mediated by a critical-collaborative action research process within the course “Teaching Practice and Supervised Internship in Spanish Language,” promote pedagogical reflection and the construction of new teaching possibilities by language teacher candidates? With the general objective of analyzing the development process and the effects/impacts of a critical-collaborative action research project, focused on the use of Digital Technologies (DT), carried out within the Teaching Practice and Supervised Internship course, aiming to understand the learning processes, reflections, and the construction of pedagogical practices for language teaching by undergraduate students in the Language and Literature program. The theoretical framework is based on studies in cyberculture, multiliteracies, TPACK, ODEA, and national teacher education policies. The study adopted a qualitative interpretivist approach, using critical-collaborative action research as its methodology. Data were collected during the Teaching Practice and Supervised Internship course, involving four fourth-year students. Instruments included semi-structured interviews, field notes, and document analysis, interpreted through Discursive Textual Analysis (Moraes & Galiazzi, 2006, 2016). The central argument is that DT can serve as catalysts for reflection and innovation in the practices of future language teachers during their initial training. Results showed that although the participants used digital technologies in their daily lives, they faced challenges in transferring this knowledge to pedagogical practices. During their training, some teacher educators employed digital tools, but rarely explored their pedagogical potential. Document analysis revealed that the topic was scarcely addressed in curriculum documents, appearing in only one course within the Political-Pedagogical Project and with limited detail. During the supervised internship, participants developed activities using digital resources, supported by the course instructor, although most remained at the initial levels of the SAMR model. Those with previous experience in teaching and with DT demonstrated greater ease in integrating these resources into their planning and practice. It is concluded that the initial teacher education program investigated was only partially aligned with contemporary expectations, revealing the need for stronger connections between theory and practice in the use of DT, less curricular fragmentation, and more immersive experiences in digital contexts during teacher education.